Associations of maternal night shift work during pregnancy with DNA methylation in offspring: a meta-analysis in the PACE consortium - Marques, Irene F.; Domènech-Panicello, Carola; Geurtsen, Madelon L.; Hoang, Thanh T.; Richmond, Rebecca; Polinski, Kristen; Sirignano, Lea; Page, Christian M.; Binter, Anne-Claire; Everson, Todd; Burt, Amber; Deuschle, Michael; et al. (Clinical epigenetics, 2025)
Night shift work during pregnancy has been associated with differential DNA methylation in placental tissue, but no studies have explored this association in cord blood. We aimed to examine associations of maternal night shift work with cord blood DNA methylation. A total of 4487 mother-newborn pairs from 7 studies were included. Maternal night shift work during pregnancy was ascertained via questionnaires and harmonized into “any” versus “no”. DNA methylation was measured in cord blood using the Illumina Infinium Methylation arrays. Robust linear regression models adjusted for relevant confounders were run in the individual cohorts, and results were meta-analyzed. Maternal night shift work during pregnancy ranged from 3.4% to 26.3%. Three CpGs were differentially methylated in relation to maternal night shift work during pregnancy at a false discovery rate adjusted P < 0.05: cg10945885 (estimate (β) 0.38%, standard error (SE) 0.07), cg00773359 (β 0.25%, SE 0.05), and cg21836426 (β − 0.29%, SE 0.05). Associations of the identified CpGs were found in previous literature for gestational age and childhood and adolescent BMI. In a mouse model of prenatal jet lag exposure, information on offspring DNA methylation of ten homologous genes annotated to the 16 CpGs with P < 1 × 10−5 in our analysis was available, of which eight were associated (enrichment P: 1.62 × 10−11). Maternal night shift work during pregnancy was associated with newborn DNA methylation at 3 CpGs. Top findings overlapped with those in a mouse model of gestational jet lag. This work strengthens evidence that DNA methylation could be a marker or mediator of impacts of circadian rhythm disturbances.
Gesehen am 31.07.2025